2020
DOI: 10.1177/1177932220909851
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Based Clustering Algorithms: Comparison Between Denclue, Fuzzy-C, and BIRCH

Abstract: The current study seeks to compare 3 clustering algorithms that can be used in gene-based bioinformatics research to understand disease networks, protein-protein interaction networks, and gene expression data. Denclue, Fuzzy-C, and Balanced Iterative and Clustering using Hierarchies (BIRCH) were the 3 gene-based clustering algorithms selected. These algorithms were explored in relation to the subfield of bioinformatics that analyzes omics data, which include but are not limited to genomics, proteomics, metagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While BIRCH can solve big data sets with faster execution times, the quality of the generated clusters remains subpar [10]. The benefit of BIRCH is that it can infer the best subcluster that can be obtained while limiting input/output while gradually producing the highest quality clusters, which is useful when other methods struggle to handle outliers and huge datasets [19]. The steps of the BIRCH algorithm are as follows [20].…”
Section: Birchmentioning
confidence: 99%
“…While BIRCH can solve big data sets with faster execution times, the quality of the generated clusters remains subpar [10]. The benefit of BIRCH is that it can infer the best subcluster that can be obtained while limiting input/output while gradually producing the highest quality clusters, which is useful when other methods struggle to handle outliers and huge datasets [19]. The steps of the BIRCH algorithm are as follows [20].…”
Section: Birchmentioning
confidence: 99%
“…42 At that time, the study encountered and reported problems relating to gene prediction, annotation and alignment. Although bioinformatics methods and databases have since advanced 43 leading to improvements in multiple sequence alignment, determination of gene regulatory networks and prediction of subcellular localisation, many genes are still poorly annotated which represents a challenge for pathogen detection when implementing comparative genomics. However, these examples show how genomics can and have been proactively applied in the identification of virulent bio-threats.…”
Section: How Genomics Can Be Applied To Proactively Prevent An Outbreak?mentioning
confidence: 99%
“…In this method, similar data are grouped in the same cluster as in Figure 4, and the data outside these groups are determined as noise and either deleted or its value is changed to the closest cluster. K-means [27], DBSCAN [28], BIRCH [29] and OPTICS [30] are commonly used clustering algorithms. Schelling and Plant [31] made improvements to the standard Kmeans algorithm, which uses clustering method for noise detection, and increased its performance.…”
Section: Ensemble Filter (Ef)mentioning
confidence: 99%